SOME ASPECTS OF UNDERSTANDING WOMEN IN RADMILA LAZIC'S FOLK BALLADS AND POETRY (Heritage, 2020)
Woman in folk ballads has numerous roles and functions, so her character in this songs in divergent and complex. She is often forced to choose between her own feelings and obeying rules of patriarchal society. Woman in this folk genre in general has traditional beliefs, unlike the lyric subject in Radmila Lazić’s poetry, which tends to become modern – to emancipate itself. In accordance to this, the lyric subject in poetry of the contemporary poet tries to reevaluate patriarchal code. In the paper we analysed these „two” womеn, the one from folk ballads and the one from Radmila Lazić’s songs. We showed that they are not as different as we thought аt first.
Keywords: folk ballads, Radmila Lazić, poetry, woman, traditional/modern